Macroevolutionary patterns in overexpression of tyrosine: An anti‐herbivore defence in a speciose tropical tree genus, Inga (Fabaceae). (30th May 2019) - Coley, Phyllis D.; Endara, María‐José; Ghabash, Gabrielle; Kidner, Catherine A.; Nicholls, James A.; Pennington, R. Toby; Mills, Anthony G.; Soule, Abrianna J.; Lemes, Maristerra R.; Stone, Graham N.; Kursar, Thomas A.
Abstract: Plant secondary metabolites are a key defence against herbivores, and their evolutionary origin is likely from primary metabolites. Yet for this to occur, an intermediate step of overexpression of primary metabolites would need to confer some advantage to the plant. Here, we examine the evolution of overexpression of the essential amino acid, L‐tyrosine and its role as a defence against herbivores. We examined overexpression of tyrosine in 97 species of Inga (Fabaceae), a genus of tropical trees, at five sites throughout the Neotropics. We predicted that tyrosine could act as an anti‐herbivore defence because concentrations of 4% tyrosine in artificial diets halved larval growth rates. We also collected insect herbivores to determine if tyrosine and its derivatives influenced host associations. Overexpression of tyrosine was only present in a single lineage comprising 21 species, with concentrations ranging from 5% to 20% of the leaf dry weight. Overexpression was pronounced in expanding but not in mature leaves. Despite laboratory studies showing toxicity of L‐tyrosine, Inga species with tyrosine suffered higher levels of herbivory. We therefore hypothesize that overexpression is only favoured in species with less effective secondary metabolites. Some tyrosine‐producing species also contained secondary metabolites that are derived from tyrosine: tyrosine‐gallates, tyramine‐gallates and DOPA‐gallates. Elevated levels of transcripts of prephenate dehydrogenase, an enzyme in the tyrosine biosynthetic pathway that is insensitive to negative feedback from tyrosine, were found only in species that overexpress tyrosine or related gallates. Different lineages of herbivores showed contrasting responses to the overexpression of tyrosine and its derived secondary metabolites in their host plants. Synthesis . We propose that overexpression of some primary metabolites can serve as a chemical defence against herbivores, and are most likely to be selected for in species suffering high herbivory due to less effective secondary metabolites. Overexpression may be the first evolutionary step in the transition to the production of more derived secondary metabolites. Presumably, derived compounds would be more effective and less costly than free tyrosine as anti‐herbivore defences. Abstract : We propose that overexpression of some primary metabolites can serve as a chemical defence against herbivores, and are most likely to be selected for in species suffering high herbivory due to less effective secondary metabolites. Overexpression may be the first evolutionary step in the transition to the production of more derived secondary metabolites. Presumably, derived compounds would be more effective and less costly than free tyrosine as anti‐herbivore defences. Resumen: Los metabolitos secundarios de plantas son una defensa clave contra herbívoros, y, probablemente, se originaron evolutivamente desde metabolitos primarios. Sin embargo, para que esto suceda, un paso intermedio de sobreexpresión de metabolitos primarios debería conferir algún tipo de ventaja a la planta. En este estudio, examinamos el origen evolutivo de la sobreexpresión de un amino ácido esencial, L‐tirosina, y su rol como defensa contra herbívoros. Examinamos la sobreexpresión de tirosina en 97 especies de Inga (Fabaceae), un género de árboles tropicales, en cinco sitios a lo largo del Neotrópico. Predecimos que la tirosina podría actuar como una defensa anti‐herbívoro debido a que concentraciones de 4% de tirosina en dietas artificiales disminuyeron en la mitad la tasa de crecimiento de larvas. También colectamos insectos herbívoros para determinar si la tirosina y sus derivados influyeron en la asociación con hospederos. La sobreexpresión de tirosina estuvo presente en un solo linaje que comprende a 21 especies, con concentraciones entre 5‐20% del peso seco de la hoja. La sobreexpresión fue pronunciada en hojas en expansión pero no en hojas maduras. A pesar de que estudios de laboratorio demostraron toxicidad de L‐tirosina, las especies de Inga con tirosina sufrieron mayores niveles de herbivoría. Por lo tanto, nosotros hipotetizamos que la sobreexpresión es únicamente favorecida en especies con metabolitos secundarios menos efectivos. Algunas especies productoras de tirosina también contienen metabolitos secundarios que son derivados de tirosina: galatos de tirosina, galatos de tiramina y galatos DOPA. Niveles elevados de transcritos de prefenato deshidrogenasa, una enzima de la vía biosintética de la tirosina que es insensible a la retroalimentación de la tirosina, fueron encontrados únicamente en especies que sobre‐expresan tirosina o galatos relacionados. Diferentes linajes de herbívoros demostraron contrastantes respuestas a la sobreexpresión de la tirosina y sus metabolitos secundarios en sus plantas hospederas. Síntesis . Proponemos que la sobreexpresión de algunos metabolitos primarios puede servir como una defensa química contra herbívoros, y que son más probables a ser seleccionados en especies que sufren altos niveles de herbivoría debido a metabolitos secundarios menos efectivos. La sobreexpresión podría ser el primer paso evolutivo en la transición hacia la producción de metabolitos secundarios más derivados. Presumiblemente, los compuestos derivados podrían ser más efectivos y menos costosos que la tirosina libre como una defensa anti‐herbívoro.